ANALISIS PERBANDINGAN ANTARA TINGKAT KESEHATAN BANK PEMBANGUNAN DAERAH DENGAN BANK UMUM LAINNYA - Purwanto Purwanto (STIE Trisna Negara OKU Timur, 2019)
Community development banks has different characteristics with groups of other commercial banks. In addition to running the activities of commercial banks, Community development banks also serves as a driver of regional agent of development. Community development banks prosecuted still play a role in facilitating regional development funds, both investment projects and working capital. Community development banks also serves as a cashier local governments, such as the realization of budget funds. The aim of this study was to determine the performance comparison between Community development banks and other national private commercial bank. Research using banking statistics sourced from Bank Indonesia (2013). The analysis was performed with descriptive approach. The study found that Community development banks has profitability, efficiency and liquidity is better than other commercial banks. Judging from the aspect of capital and productive quality, Community development banks has a CAR and lower asset quality of commercial banks Others, while viewed from the aspect of liquidity (LDR) were not statistically different.